Antimicrobial and physicochemical characterization of whey protein concentrate edible films incorporated with liquid smoke - Soazo, Marina del Valle (2016)
The incorporation of commercial liquid smoke (LS) to edible films was investigated for the first time. The objective of this investigation was to characterize whey protein concentrate (WPC)-based edible films incorporated with LS. According to the bactericidal activity of LS against Escherichia coli, Staphylococcus aureus, Salmonella Typhimurium, and Listeria monocytogenes in liquid medium, WPC-based films incorporated with 0, 5, 10, and 15% (v/v) LS were prepared. Inhibition zone in solid media, thickness, transparency, color and mechanical properties of the films were analyzed. Films including LS were effective to prevent growth of L. monocytogenes in the agar diffusion test. Analyzing color parameters, the incorporation of LS into films caused a decrease in L* and an increase in both a* and b*. However, these sensory changes were not detrimental for their potential use in food applications. Noticeably, tensile strength and elongation tend to increase when LS was added into films formulation. Depending on its content, different protein-LS interactions could be generated, positively affecting the mechanical properties of films. In conclusion, WPC-based edible films incorporated with LS may be suitable for being applied to food surfaces and useful to prevent the superficial growth of the globally recognized high-risk foodborne pathogen Listeria monocytogenes.